A novel graphene hybrid for reducing fire hazard of epoxy resin. (19th December 2017) - Xu, Wenzong; Wang, Xiaoling; Wang, Guisong; Li, Aijiao; Xu, Baoling
Abstract : Epoxy resin (EP) is more and more important in many fields, but its application is limited due to the inflammability in air of EP. Therefore, reducing the fire hazard of EP is necessary. In this work, a kind of hybrid flame retardant (α‐ZrP‐RGO) consisting of a 2‐dimensional inorganic reduced graphene oxide (RGO) modified with a planar‐like α‐zirconium phosphate (α‐ZrP) particles was prepared successfully via 1‐step hydrothermal method. The effects of α‐ZrP‐RGO on the thermal performance, flame retardancy, and smoke suppression of EP were investigated by preparing EP composites containing both EP and α‐ZrP‐RGO. Thermogravimetric results revealed that α‐ZrP‐RGO could improve the char yield of EP at 700°C obviously. In addition, compared with pure EP, the peak heat release rate and the total heat release of EP composites were decreased significantly, while the limited oxygen index of EP composites was increased. Meanwhile, the smoke production rate of EP composites was reduced obviously with the addition of α‐ZrP‐RGO. The enhanced flame retardancy and smoke suppression of EP composites were mainly attributed to not only the physical barrier effect of both α‐ZrP and RGO but also the catalytic effect of α‐ZrP during the combustion process of EP composites.